Extraction of Collagen from Kedukang Fish Bone (Hexanematichthys sagor) at Various Concentrations of Acetic Acid Solution - Veronica, Veronica; Junianto, Junianto; Aulia Andhikawati; Emma Rochima (Grouper, 2025)
The bones of kedukang fish, a by-product of jambal roti production in Pangandaran, have the potential to be a source of collagen. Collagen extraction can be done chemically using acetic acid solution. The extraction process is declared effective if it produces optimal collagen yield. This study aims to determine the best acetic acid concentration in producing optimal collagen yield. The research was conducted from December 2024 to February 2025 at the Tropical Marine Fisheries Laboratory and Central Laboratory of Padjadjaran University and the Center for Testing and Application of Fishery Product Quality (BP2MHP) Semarang. The method used was experimental method, namely the difference in acetic acid concentration in collagen extraction with three treatments (0.5 M; 0.75 M; and 1 M). Parameters observed included yield, physicochemical characteristics and functional groups of collagen from the best treatment. Based on the results, 1 M acetic acid concentration treatment was the best treatment with a yield value of 34.62% ± 1.31. The characteristics of collagen produced include moisture content of 9.507%, ash content of 2.60%, protein content of 64.91% and pH 6.94. FTIR results showed collagen identified Amide A at the absorption peak of 3404 cm-¹, Amide I at the absorption peak of 1698.40 cm-¹ and 1636.98 cm-¹, Amide II at the absorption peak of 1546.40 cm-¹ and Amide III at the absorption peak of 1230.36 cm-¹.